2021
DOI: 10.26480/jcleanwas.02.2021.78.84
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Salt Dust Caused by Drying of Urmia Lake on the Sustainability of Urban Environments

Abstract: Due to the gradual drying of parts of Urmia Lake, several centers of salt dust which is created and influence the agriculture, economy, public health and causes migrations within the region of the Urmia Lake. Hence, knowing the temporal and spatial distribution of this phenomenon is very important to quantify these effects. In the present study, using Sentinel-5 and MODIS products for 2020 in the Google Earth system, have shown despite month-to-month fluctuations, has an increasing trend and the incremental ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The number of dusty days has fallen sharply in the summer, with the least in August. Thus, dust mostly occurs in May (spring), as mentioned in [27], and October (autumn), contrary to what has been presented by Shahkooeei and Rahmani (2019) [24] as a minor dust occurrence. Significant dust was recorded in June in Mahabad, which is because Mahabad is close to neighboring dust sources in Iraq, as described in previous sections.…”
Section: Temporal Distribution Of Dust-related Meteorological Conditionscontrasting
confidence: 56%
See 1 more Smart Citation
“…The number of dusty days has fallen sharply in the summer, with the least in August. Thus, dust mostly occurs in May (spring), as mentioned in [27], and October (autumn), contrary to what has been presented by Shahkooeei and Rahmani (2019) [24] as a minor dust occurrence. Significant dust was recorded in June in Mahabad, which is because Mahabad is close to neighboring dust sources in Iraq, as described in previous sections.…”
Section: Temporal Distribution Of Dust-related Meteorological Conditionscontrasting
confidence: 56%
“…Dust has influenced agriculture, the economy, and human life, including health and migration, in northwest Iran from 2019 to 2020 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies also confirmed that drought leads to airborne salt-dust scatter 7 , 14 , 31 33 . When the saline flow sources around the lake are activated during monsoon season, they emit a wave of salt-dust into the air that can reach the neighboring cities 34 .…”
Section: Study Areamentioning
confidence: 64%
“…Satellite imagery emerges as a formidable instrument, wielding the power to discern, map, and vigilantly oversee regions prone to these perils, thus contributing to risk mitigation and the fortification of disaster preparedness, as delineated in the works of Majidi et al (2022) and Qasimi et al (2022). Remote sensing data assumes a pivotal role in the identification and continuous monitoring of an array of natural phenomena, spanning earthquakes, landslides, wildfires, and hurricanes, as evidenced by the research conducted by Isazade et al (2021;2022). By amalgamating remote sensing data with other geospatial information, researchers and emergency response teams can better comprehend the magnitude of destruction caused by natural calamities.…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive review provides an overarching perspective on remote sensing applications across various geographic disciplines, encompassing land cover mapping, vegetation analysis, urban studies, water resources management, and natural hazard assessment. Integrating remote sensing data with GIS and the latest advances in artificial intelligence holds substantial promise for the future of geographic research (Isazade et al, 2021). However, challenges related to data availability, accuracy, and advanced analytical techniques must be addressed to harness the benefits of remote sensing fully Hinton, 1996;Yao, 2021;Zhang et al, 2011aZhang et al, , 2011b.…”
Section: Introductionmentioning
confidence: 99%